The treatment of tonsillar squamous cell carcinoma at hue central hospital - Nam, Tran Phuong; Thong, Le Chi; Dat, Duong Manh; Thanh, Le Viet (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Objective: To explore some clinical features, treatment selection and middle-term outcomes of patients with tonsillar squamous cell carcinoma at Hue Central Hospital. Methods: A prospective study was conducted in a total of 29 patients with squamous cell carcinoma of the tonsil who had been diagnosed and treated at Hue Central Hospital from 1/2018 to 6/2020. Results: Patients aged over 50 years old were the most seen (accounted for 69%). The mean of age was 57.1 ± 12.8, the ratio of male and female was 1.4/1. The major reason was odynophagia (accounted for 69%). Patients in advanced stage were most often. The cumulative survival rate at 24 months and advanced-stage were 85,7%, 63,6% respectively. All patients with primary surgery followed by adjuvant radiotherapy were still alive in follow-up period, 30 months. The cumulative survival rate of the palliative treatment group at 12 months was 21.9%. Conclusion: Primary surgery followed by adjuvant radiotherapy is an effective treatment of squamous cell carcinoma of the tonsil. Keywords: Tonsillar squamous cell carcinoma, surgery